Developing a supply chain coordination model through a revised revenue sharing contract: Incorporating sales efforts and green quality considerations - Mahdi Nakhaeinejad; Abolfazl Dehghan; Nayereh Sadat Vaziri (International Journal of Production Management and Engineering)
In response to the growing emphasis on supply chain sustainability and green business management, this study addresses the critical challenges faced by industries in balancing the costs and benefits of enhancing the green quality of products, pricing strategies, and sales efforts. As environmentally conscious consumers increasingly prefer products from sustainable supply chains, industries encounter the dilemma of investing in sustainable practices while maintaining profitability. This research identifies the need for effective decision optimization models and coordination mechanisms that incentivize supply chain members to collaborate towards sustainable production without compromising their financial goals. To this end, we propose a novel hybrid cost and revenue sharing (HCRS) contract designed to foster collaboration among supply chain partners and align their interests in promoting sustainability. By examining optimal decision-making conditions, coordination mechanisms, and profit-sharing arrangements, the study highlights how the implementation of the HCRS contract can lead to improved supply chain performance and profitability. Our findings indicate that an increase in customer sustainability consciousness (CSC) positively correlates with higher levels of product green quality and overall profit, illustrating the potential benefits of prioritizing sustainability in supply chain operations.